A Young Lady with Unilateral Sudden Painful Complete Ophthalmoplegia: Tolosa- Hunt Syndrome (Bangladesh Journal of Neuroscience, 2026)
Tolosa–Hunt syndrome (THS) is a painful ophthalmoplegia characterized by recurrent unilateral periorbital or hemicranial pain, ipsilateral ocular motor nerve paralysis, oculosympathetic paralysis, sensory loss in the distribution of the ophthalmic and occasionally the maxillary division of the trigeminal nerve and a rapid response to steroids. Various combinations of these cranial nerve palsies may occur, localizing the pathological process to the region of the cavernous sinus/superior orbital fissure. Our report describes a 40-year-old young lady who presented with sudden, severe right hemicranial and periorbital pain with ipsilateral 3rd,4th, 6th cranial nerve palsies along with ophthalmic division of trigeminal nerve involvement. MRI of orbit showed hypointense lesion in right cavernous sinus extending to right superior orbital fissure (suggestive of granulomatous infiltration). THS is a diagnosis of exclusion. After taking oral steroid her pain was relieved quickly and cranial nerve palsies reversed within two weeks.